2013
DOI: 10.1038/nrurol.2013.196
|View full text |Cite
|
Sign up to set email alerts
|

MRI-targeted prostate biopsy: a review of technique and results

Abstract: Multiparametric magnetic resonance imaging (mpMRI) is of interest for the diagnosis of clinically significant prostate cancer and mpMRI-targeted biopsies are being used increasingly in clinical practice. Target acquisition is performed using a range of magnet strengths and varying combinations of anatomical and functional sequences. Target identification at the time of biopsy can be carried out in the MRI scanner (in-bore biopsy) or, more commonly, the MRI-target is biopsied under ultrasonographic guidance. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 70 publications
1
32
0
1
Order By: Relevance
“…Several studies have indicated increased overall diagnostic accuracy for a multiparametric approach, defined as the combination of one structural and at least two functional MRI techniques providing morphological tissue information with T2-weighted MRI (T2W-MRI) and functional tissue information, such as tissue perfusion with dynamic contrast-enhanced MRI (DCE-MRI), or restriction of water solubility with diffusion-weighted imaging (DWI) [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated increased overall diagnostic accuracy for a multiparametric approach, defined as the combination of one structural and at least two functional MRI techniques providing morphological tissue information with T2-weighted MRI (T2W-MRI) and functional tissue information, such as tissue perfusion with dynamic contrast-enhanced MRI (DCE-MRI), or restriction of water solubility with diffusion-weighted imaging (DWI) [4]. …”
Section: Introductionmentioning
confidence: 99%
“…These have been reviewed in several recent meta-analyses (13)(14)(15)(16). In essence, there are six configurations from which to choose: The navigation or guidance method can be transrectal US or MR imaging, samples can be taken either in the bore or outside the magnet, and the access route can be either transrectal or transperineal.…”
Section: Implication For Patient Carementioning
confidence: 99%
“…Moderne bildgebende Techniken haben mittlerweile bewiesen, dass sie relativ zuverlässig signifikante Prostatakarzinome nachweisen können [4]. Daher kommt der Visualisierung des Prostatakarzinoms eine wichtige Rolle zu.…”
Section: Hintergrundunclassified